Words are monuments: Patterns in US national park place names perpetuate settler colonial mythologies including white supremacy - Bonnie M. McGill; Stephanie B. Borrelle; Grace C. Wu; Kurt E. Ingeman; Jonathan Berenguer Uhuad Koch; Natchee B. Barnd (People and Nature, 2022)
Abstract Ecologists, outdoor professionals and the public work and play in lands with complex histories. Part of decolonizing our professional and recreational practices is to expose settler colonial biases and recognize the histories of colonized lands and the peoples who have stewarded these lands for millennia prior to colonization. To provide a quantitative example of settler colonial biases in a familiar context, we examined the origins of over 2,200 place names in 16 national parks in the United States (US; 26% of the parks). Through iterative thematic analysis of place name origins and meanings, we constructed a decision tree for classifying place names according to emergent categories, which enabled the quantification and spatial analysis of place name meanings. All national parks examined have place names that tacitly endorse racist or, more specifically, anti‐Indigenous ideologies, thus perpetuating settler colonialism and white supremacy at the system scale for future generations. Looking east to west across the US, the proportion of place names per national park that appropriated Indigenous names increased in parallel with the westward expansion and evolution of US settler colonialism. This examination of place names, name origins and their consequences is an opportunity to make everyday complicity in systemic oppression more visible and to more actively advance decolonizing practices for land and language. Read the free Plain Language Summary for this article on the Journal blog.